The Level of Loyalty of Pet Owners to Their Animals in Türkiye - Alan, Seda Çavuş; Ozen, Abdullah (My University, 2024)
An understanding of the nature of the relationship between the pet owner and his companion animal and the factors influential on this bond is critical to the establishment of a healthy relationship between both sides. This study was aimed at measuring the level of loyalty of pet owners to their animals and identifying the factors influential on this commitment. For this purpose, a survey consisting of the Pet Loyalty Scale and demographic information items was administered face to face to 300 pet owners in Istanbul (150), Ankara (60) and Izmir (90). The results of this study showed that while the level of loyalty of the owner to the pet animal decreased with the increasing age of the survey participants (p<0.01), it increased with the increasing age of the pet animal (p<0.05). The assessment of the gender and marital status parameters demonstrated that women, compared to men (p<0.01), and singles, compared to married individuals (p<0.05), were more loyal to their pets. Furthermore, the loyalty of the pet owners to their animals decreased with an increasing income level (p<0.001), but increased with an increasing monthly cost of keeping the pet animal (p<0.05). In conclusion, we determined that the young compared to the elderly, female compared to male, and singles compared to married persons displayed higher levels of loyalty to their pet animals. Moreover, respondents with a lower level of income and those paying for a higher cost to keep their pets also showed higher levels of loyalty to their pets.
Keywords: Sosyal Çalışma; Sosyoloji